(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2026)
The current research aims to analyze the impact of implementing smart cost accounting systems on the efficiency of financial performance measurement in Iraqi commercial banks. The research problem stems from the limited use of these systems within the Iraqi banking environment, despite the rapid global digital transformations. This weakens banks’ ability to provide accurate and flexible financial information that supports management decisions. The applied aspect of the research was conducted at Rafidain Bank in Baghdad using a scientific questionnaire reviewed by four experts to ensure internal validity and the accuracy of indicators. (63) questionnaires were distributed to employees of the relevant departments, and (57) valid questionnaires were analyzed using SPSS version (25). The results showed that the implementation of smart technology-based cost accounting systems at Rafidain Bank led to a significant improvement in the accuracy and effectiveness of measuring financial and operational performance, contributing to faster and more accurate management decisions that supported improved institutional performance. The research recommended the need to promote the adoption of smart cost accounting systems at Rafidain Bank and other Iraqi banks to accelerate the administrative decision-making process and support the enhancement of institutional efficiency.